Terrorism-related assessments - Gill, Paul (Seminars in forensic psychiatry, 2024)
This chapter is about forensic psychiatric assessment of terrorism cases. As will become clear, this may not be a straightforward exercise in that it can be difficult to decide whether the case actually involves terrorism, let alone what contribution mental disorder may or may not make. Nonetheless, psychiatric assessment is often requested and assessment of the terrorism offender relies on the same basic principles of good-quality assessment, utilising a multi-agency approach, that is applicable when assessing any complex criminal, or potentially criminal, behaviour involving mental disorder.